Validation Exercise of GeoAgro-Misr Egypt Use Case - Attaher, Samar; Govind, Ajit; Nangia, Vinay (2025)
The agrifood systems in global drylands face significant impacts of climatic challenges, including extreme temperatures, variable rainfall, and declining water resources. These challenges are compounded by socioeconomic and political issues, which is adding more challenges to small-holder farmers1. Egypt, positioned within this region, exemplifies the impact of climate stress on agriculture, experiencing a growing increase in heat stress and crop-water consumption, rising groundwater and soil salinity, extended extreme events, significant changes in the crop-life cycle, and shifting planting seasons that significantly affect its crucial agriculture sector. This sector supports 65% of Egypt's population and contributes 14.5% to GDP. Adaptation strategies, particularly for small-holder farmers, must be integrated into comprehensive agendas to address food insecurity, land fragmentation, soil degradation, and unsustainable practices amid economic pressures, ensuring resilience and long-term peace. In this context, Egypt's climate-related challenges serve as a representative sample of the broader climate issues confronted by the global drylands, highlighting the shared imperative of addressing these issues to foster stability and prosperity.